Sosialiasi wakaf: Peningkatan leterasi wakaf uang melalui sosialiasi pada masyarakat kampus - Annisa, Arna Asna; Rofiuddin, Mohammad (Nur Science Institute, 2023)
The problem related to waqf that is being faced now is that the gap between the potential of cash waqf and the reality of the cash waqf movement is still far away, so there is a need to increase waqf literacy, especially cash waqf. The service method is carried out by socialization, and in the next stage, an evaluation is carried out using the Paired Sample t-test. The service results show an increase in understanding of the academic community of IAIN Salatiga before and after the socialization of waqf literacy. In addition, there needs to be innovation in distributing waqf knowledge to all elements of the Muslim community. There are suggestions from the results of the dedication evaluation that the socialization of waqf must be massive, especially in campus areas and Islamic boarding schools. Furthermore, socialization is carried out innovatively by utilizing social media so that it will be straightforward to reach young people, millennials, or generation Z.